2007
DOI: 10.1161/strokeaha.106.478230
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Laser Therapy for Ischemic Stroke: A New Treatment Strategy

Abstract: Background and Purpose-The NeuroThera Effectiveness and Safety Trial-1 (NEST-1) study evaluated the safety and preliminary effectiveness of the NeuroThera Laser System in the ability to improve 90-day outcomes in ischemic stroke patients treated within 24 hours from stroke onset. The NeuroThera Laser System therapeutic approach involves use of infrared laser technology and has shown significant and sustained beneficial effects in animal models of ischemic stroke. Methods-This was a prospective, intention-to-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0
23

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(172 citation statements)
references
References 22 publications
2
141
0
23
Order By: Relevance
“…Today, specific wavelengths in the red and near infrared ranges (ca 600-1200 nm) are known to stimulate a wide array of biological processes ranging from the expansion of cardiac stem cells in culture [148] to accelerated healing of chemotherapy-associated mucositis [149]. Low level laser treatment using an 808 nm light source has even shown promise in a blinded, prospective clinical trial in acute stroke patients [150].…”
Section: Optics Biophotonics and Nanotechnologiesmentioning
confidence: 99%
“…Today, specific wavelengths in the red and near infrared ranges (ca 600-1200 nm) are known to stimulate a wide array of biological processes ranging from the expansion of cardiac stem cells in culture [148] to accelerated healing of chemotherapy-associated mucositis [149]. Low level laser treatment using an 808 nm light source has even shown promise in a blinded, prospective clinical trial in acute stroke patients [150].…”
Section: Optics Biophotonics and Nanotechnologiesmentioning
confidence: 99%
“…It is one thing for NIr to influence SNc survival 4-5 mm inside the skull of a mouse, and quite another to reliably influence SNc survival 80-100 mm inside the skull of a human. Indeed, almost all current clinical studies reporting the beneficial effects of NIr treatment have involved cases in which the target region was in the cortex, lying only 8-10 mm below the cranium, 19 whether in patients suffering trauma, 27 stroke, 17,19 or depression. 36 Structures lying much deeper in the human brain, such as in the SNc, may be largely beyond the range of externally applied NIr.…”
mentioning
confidence: 99%
“…[8,14] Positive sham-controlled studies in acute stroke patients included the single T-LLT stimulation of 20 points according to the 10-20 system for one minute each, the wave length was 808 nm and the intensity 10 mW/cm 2 . [15,16,17] In embolized rabbit's brain, Lapchak and De Taboada successfully showed that T-LLT (wave length 808 nm, intensity 10 mW/cm 2 ) significantly increased the cortical ATP, the penetration depth was 20 -30 mm. [18] Accordingly the authors of the acute stroke studies speculated that the transcranial laser could have activated the respiratory chain, namely the complex IV, thus increasing the ATP production and helping cell recuperation.…”
Section: Discussionmentioning
confidence: 99%